2010
DOI: 10.1103/physrevlett.104.076402
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Orbit Strength Driven Crossover between Intrinsic and Extrinsic Mechanisms of the Anomalous Hall Effect in the EpitaxialL10-Ordered Ferromagnets FePd and FePt

Abstract: We determine the composition of intrinsic as well as extrinsic contributions to the anomalous Hall effect (AHE) in the isoelectronic L1_{0} FePd and FePt alloys. We show that the AHE signal in our 30 nm thick epitaxially deposited films of FePd is mainly due to an extrinsic side jump, while in the epitaxial FePt films of the same thickness and degree of order the intrinsic contribution is dominating over the extrinsic mechanisms of the AHE. We relate this crossover to the difference in spin-orbit strength of P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
78
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 28 publications
9
78
1
Order By: Relevance
“…4(c). This is because the ξ is 0.6, 0.20, and 0.06 (eV) for Pt, Pd, and Fe atoms, respectively 27,38 and the effect of Fe atoms is negligible compared with those of Pd and Pt atoms. The present results of ξ are in good agreement with previous ab initio calculations 38 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4(c). This is because the ξ is 0.6, 0.20, and 0.06 (eV) for Pt, Pd, and Fe atoms, respectively 27,38 and the effect of Fe atoms is negligible compared with those of Pd and Pt atoms. The present results of ξ are in good agreement with previous ab initio calculations 38 .…”
mentioning
confidence: 99%
“…The orbital momentum in 3d magnetic metallic films restored by the SOC is also proportional to the ξ and the PMA therefore is proportional to ξ 2 /W with the bandwidth of 3d electrons W 36 . Since the W does not change much with x, the enhanced PMA at high x is attributed to a larger ξ of Pt atoms compared with that of Pd atoms 27,37 . Our calculations show ξ change from 0.20, 0.26, 0.41 to 0.58 (eV) when x varying from 0, 0.5, 0.75, to 1.0, as shown in Fig.…”
mentioning
confidence: 99%
“…In this region, large changes in the magnitude of the anomalous Hall current as well as relative orientation of the Hall current with respect to the magnetization can be easily achieved by simple reorientation of the sample's magnetization. While the former could be used in order to, e.g., tune the relative magnitudes of the extrinsic and intrinsic anomalous Hall signal, 6,29 among the most straightforward applications of the latter could be a realization of the planar Hall effect (PHE), 38 which is related to the Hall effect in ferromagnetic materials observed in a two-dimensional geometry with electric field, with magnetization and the Hall current sharing the same sample plane. So far, it is believed that, in most of the cases, the PHE originates from anisotropic magnetoresistance in metallic ferromagnets, although the PHE mechanism stemming from the anomalous Hall effect due to noncollinearity of the magnetization in semiconductor-based materials has been also suggested.…”
Section: Anisotropic Ahc In 3dpt Alloysmentioning
confidence: 99%
“…27 Recently, the AHE in FePt was used for injection of a spin-polarized current for consequent detection of direct and inverse spin Hall effect in Au. 28 In a combined experimental and theoretical study, 29 it was shown that the intrinsic contribution to the anomalous Hall signal dominates in samples of FePt with finite structural disorder. All this motivated our study of the anisotropy of the intrinsic AHE in uniaxial 3dPt alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It is widely accepted that there are three mechanisms responsible for the AHE. The intrinsic AHE arises from the transverse velocity of the Bloch electrons induced by SOI and interband mixing, 9 as experimentally evidenced by quantum anomalous Hall effect.…”
mentioning
confidence: 99%